- Penguatan Kewenangan Kementerian Komunikasi dan Informatika Memblokir Akses Konten Asusila di Media Sosial untuk Melindungi Hak Asasi Manusia.: - - Naufal Hisyam Zuhdi; Eko Primananda (Reformasi Hukum Trisakti, 2024)
Information technology crimes are increasingly varied and must be handled seriously. In this regard, the Constitutional Court through decision No. 81/PUU-XVIII/2020 has strengthened the authority of the Ministry of Information and Communication to block access to immoral content on social media, maintain the balance of human rights, and law enforcement.  The problems of this research are: how is the strengthening of the authority of the Ministry of Information and Communication in blocking access to immoral content on social media? The purpose of this study is to describe the strengthening of the authority of the Ministry of Communication and Information to block immoral content on social media. This article is a normative legal research, descriptive in nature, using secondary data, and deductive inference. The conclusion of this article, namely: the strengthening of the authority of the Ministry of Communication and Information is regulated in Law No. 19 of 2016 concerning Amendments to Law No. 1 of 2008 concerning Electronic Information and Transactions and other regulations authorizing the ministry to block access to immoral content on social media to protect human rights.